2018
DOI: 10.14744/anatoljcardiol.2018.42949
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease evaluation by coronary angiography and intracoronary imaging compared to Fractional Flow Reserve: anatomical-functional mismatch.

Abstract: Myocardial ischemia is a leading cause of death worldwide, and it corresponds to the imbalance between blood supply and myocardial demand. Epicardial coronary artery disease (CAD) is detected on the basis of coronary angiogram, whereas invasive detection of myocardial ischemia induced by coronary stenosis is commonly based on fractional flow reserve (FFR). The use of FFR for revascularization decision-making demonstrated clinical benefit and cost-effectiveness compared with that of angiographic indices. Discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Nevertheless, as established by numerous studies, it is well-documented that the relationship between the degree of coronary artery stenosis and myocardial ischemia is intricate and multifaceted. 17 , 18 Results of a study trial by Tonino et al 19 showed that 20% of the coronary arteries with over 70% stenosis had no functional ischemia. Park et al 4 showed that more than half of the coronary arteries with over 50% stenosis had an FFR value above 0.80.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as established by numerous studies, it is well-documented that the relationship between the degree of coronary artery stenosis and myocardial ischemia is intricate and multifaceted. 17 , 18 Results of a study trial by Tonino et al 19 showed that 20% of the coronary arteries with over 70% stenosis had no functional ischemia. Park et al 4 showed that more than half of the coronary arteries with over 50% stenosis had an FFR value above 0.80.…”
Section: Discussionmentioning
confidence: 99%
“…Patients requiring an FFR assessment often have diffuse atherosclerosis other than that at the site with minimal lumen diameter, which progressively decreases coronary pressure 28,29 . Unlike twodimensional angiographic projection images, FFR reflects the totality of the physiological effects of patient characteristics, lesion characteristics, microvascular function, amount of myocardial mass subtended by the coronary artery stenosis, and hyperemia 3,7,11,12,[30][31][32] . Consistent with prior studies 3,12 , non-LAD location and minimal luminal diameter were associated with an anatomical-functional mismatch.…”
Section: Anatomical-functional Mismatch and Overestimation Of Ffr By ...mentioning
confidence: 99%
“…Diameter stenosis (DS) of > 50% on invasive coronary angiography is deemed anatomically significant 1 . Coronary angiography alone, however, has limited ability to differentiate functionally significant lesions 2 7 . Pressure wire-derived fractional flow reserve (FFR) has emerged as the gold standard for assessing the functional impact of stenotic lesions, and a vessel with an FFR value ≤ 0.80 is considered to have functionally significant stenosis 2 , 8 – 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations